Kitaev honeycomb antiferromagnet in a field: quantum phase diagram for general spin - Jahromi, Saeed S.; Hörmann, Max; Adelhardt, Patrick; Fey, Sebastian; Karamnejad, Hooman; Orús, Román; Schmidt, Kai Phillip (Communications Physics, 2024)
We use tensor-network methods and high-order linked-cluster expansions to explore the quantum phase diagram of the antiferromagnetic Kitaev honeycomb model in a magnetic field for general spin S values. Tensor network calculations for the pure Kitaev model confirm the absence of fluxes and spin-spin correlations beyond nearest neighbors, while revealing discrete orientational symmetry breaking for S ∈ 1, 3/2, 2, consistent with the semiclassical limit. An intermediate region between Kitaev phases and the high-field polarized phase is identified for all considered spin values, showing a sequence of potential phases characterized by distinct local magnetization patterns while the total magnetization increases smoothly as a function of the field. Linked-cluster expansions for the high-field zero-momentum gap and spectral weight indicate a quantum critical breakdown of the polarized phase, suggesting exotic physics at intermediate Kitaev couplings.
CRIS-Team Scopus Importer:2024-10-18